Are historical conditions reference conditions? Revising the modeled riverine nutrient input into the German North Sea and Baltic Sea around 1880 - Andreas Gericke; Karoline Morling; Ingo Haag; Micha Gebel; Julia Krumm; Georges Bruns; Justus E. E. van Beusekom; Stephan Fuchs; Wera Leujak (Environmental Sciences Europe)
Abstract Background The German legislation sets two targets for riverine nitrogen concentrations in North Sea and Baltic Sea tributaries as well as river type-specific phosphorus thresholds. The current target for the Baltic Sea as well as the thresholds for the good status were derived from modeled riverine and atmospheric inputs around 1880. However, the calculated nitrogen balance differed between the model applications for the German North Sea and Baltic Sea. Existing nitrogen targets for North Sea tributaries are likely insufficient for environmental objectives according to recent model and data analyses. We used a harmonized approach to model nutrient inputs to the German Seas around 1880 and discuss these outcomes in the context of stricter requirements needed for ecological objectives in the North Sea. Results For river basins entering the German North Sea and Baltic Sea, we modeled emissions, concentrations, and loads of total nitrogen and total phosphorus around 1880. The historical riverine inputs to the North Sea were 180 kt N yr−1 and 4.20 kt P yr−1 and to the Baltic Sea 22 kt N yr−1 and 0.45 kt P yr−1, respectively. These loads corresponded to annual mean concentrations of 1.36 mg N l−1 and 0.032 mg P l−1 (North Sea) as well as 1.11 mg N l−1 and 0.022 mg P l−1 (Baltic Sea). Modeled nitrogen concentrations at river mouths were lower than the previous German model results but exceeded published reference concentrations. They were, however, partly in agreement with ecology-based concentrations for major North Sea tributaries based on published reduction needs. Conclusions The modeled nutrient concentrations at river mouths confirm the inconsistency of German model applications with regional applications. For the North Sea, they support a more stringent basin-wide nitrogen target and thresholds for the good status of coastal and marine waters. As the historical conditions exceeded reference conditions, the offset of 50% to the historical concentration for the good ecological status should be revised for both sea basins. According to ecology-based target concentrations, only + 30% may be acceptable for North Sea tributaries, corresponding to 1.8 mg N l−1. Any revision of the German legislation should acknowledge the inherent uncertainties.